Legal Protection for Exploitation of Children as Beggars in the Market by Parents in Gorontalo Regency - Arbie, Ayu Anastasya; Makkulawuzar, Kingdom; Rusmulyadi, Rusmulyadi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
The phenomenon of exploitation of child buskers is one of the social problems that must be resolved by all groups, both the government and society. This exploitation of children is even carried out by their own parents. The focus of this research study is how the form of legal protection from child exploitation should children get education but only in the market. This study aims to determine the forms of child labor exploitation, the factors that influence working children, and to determine the negative impacts arising from child exploitation. In this study, normative research on written law was examined from various aspects such as aspects of theory, philosophy, comparison, structure/composition, consistency, general explanation. This method is considered suitable by researchers to be used in describing the problem of child exploitation in the Gorontalo district market. Based on the results of this study, biological parents are involved in the form of exploitation of children in the market. Factors that influence children to work in the market are economic factors, family factors, and environmental factors. And the negative impact arising from the exploitation of children in the market is the disruption of children's health, loss of desire to go to school, the emergence of psychological traumas in children. and the emergence of unrest in the community around the red light as well as the community around where the child workers themselves live.